British Influenceon Commonwealth Budget Systems The Case of the United Republic of Tanzania - Lienert, Ian (International Monetary Fund, 2007)
Several features of Tanzania''s budget system find their roots in the arrangements inherited from the United Kingdom. These include a legal framework that emphasizes accountability; a cabinet of ministers with strong budget decision-making powers; a parliament with very limited budget powers; and a similar external audit organization. In both countries, budget execution is decentralized to individual ministries, with accounting officers responsible to a parliamentary accounts committee. These similarities are blended with contrasts, including in Tanzania: a presidential system of government, one dominant political party, a written constitution, and some fragmentation in central budget decision-making within the executive